Proline‐rich transmembrane protein 2 regulates the magnitude and frequency of dopamine release by repetitive neuronal stimuli in the striatum of L‐dopa‐treated mice - Daisuke Hatta; Shiho Makiya; Kaito Kanamoto; Kaori Watanabe; Yuki Fuchigami; Shigeru Kawakami; Akira Kinoshita; Koh‐Ichiro Yoshiura; Naohiro Kurotaki; Keiro Shirotani; Nobuhisa Iwata (Wiley, 2024)
Abstract Mutations in proline‐rich transmembrane protein 2 (PRRT2) cause paroxysmal kinesigenic dyskinesia (PKD). Recently, we reported that a Prrt2 mutation exacerbated L‐dopa‐induced motor deficits in mice, suggesting that the basal ganglia might contribute to PKD pathology. Here, we demonstrated that the Prrt2 mutation enhanced depolarization stimuli‐induced extracellular dopamine levels in the mouse striatum, which were attenuated by repeated stimulation. L‐dopa administration maintained high dopamine levels in Prrt2‐KI mice even during repetitive stimuli but did not affect dopamine levels in wild‐type mice. Thus, the enhanced and prolonged responsiveness of dopamine release in nigrostriatal dopaminergic neurons to sequential excitation may be partially implicated in Prrt2‐related dyskinesia.